2015
DOI: 10.1007/s10147-015-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Japanese phase I study of cabazitaxel in metastatic castration-resistant prostate cancer

Abstract: In this heavily pretreated Japanese population, the occurrence of neutropenia and febrile neutropenia was high, suggesting G-CSF prophylaxis may be required as part of toxicity management. However, the efficacy of cabazitaxel was consistent with global studies. ClinicalTrials.gov identifier: NCT01324583.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 13 publications
8
46
2
Order By: Relevance
“…28 In a phase 1 study of cabazitaxel in Japanese patients previously treated with chemotherapy, 29.3% of 41 patients had a PSA response. 29 Whereas in the overall study population, just 3.5% of placebo-treated patients had a confirmed PSA response, and 21.2% of placebo-treated Japanese patients (seven of 33) had a confirmed PSA response. This might be a result of the use of concomitant corticosteroids, which occurred in five of seven placebo-treated patients, but just five of 17 enzalutamide-treated patients with a confirmed PSA response.…”
Section: Discussionmentioning
confidence: 87%
“…28 In a phase 1 study of cabazitaxel in Japanese patients previously treated with chemotherapy, 29.3% of 41 patients had a PSA response. 29 Whereas in the overall study population, just 3.5% of placebo-treated patients had a confirmed PSA response, and 21.2% of placebo-treated Japanese patients (seven of 33) had a confirmed PSA response. This might be a result of the use of concomitant corticosteroids, which occurred in five of seven placebo-treated patients, but just five of 17 enzalutamide-treated patients with a confirmed PSA response.…”
Section: Discussionmentioning
confidence: 87%
“…Cabazitaxel was approved worldwide for the treatment of patients with mCRPC previously treated with a docetaxel-containing regimen [4–7]. In a phase I study of cabazitaxel in patients with mCRPC in Japan that enrolled patients up to the age of 74 years, PK parameters, safety and tolerability in Japanese patients were found to be comparable to results of previous studies in Caucasian patients, and the MTD was identified as 25 mg/m 2 [8, 9]. However the safety and antitumor activity in higher-age patients more than 74 years have not been fully characterized yet.…”
Section: Introductionmentioning
confidence: 82%
“…Cabazitaxel was the first agent demonstrating a survival benefit in Western CRPC patients progressing during or after docetaxel [1, 8, 9]. A phase I cabazitaxel study in Japan demonstrated the safety and the efficacy of PSA-PFS [8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in other studies of Asian men with mCRPC, including phase II studies of abiraterone acetate and prednisolone, in which 43% to 60% of Asian patients had a PSA response. [32,33] Similarly, in studies of cabazitaxel in Japanese [34] and Korean, [35] patients with mCRPC previously treated with chemotherapy, PSA responses were achieved by 29% and 32% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%